Nursing practice competency of accelerated bachelor of science in nursing program students. - Raines DA (Journal of Professional Nursing)
The purposes of this study were to quantify the perception of nursing practice competency by students in an accelerated bachelor of science in nursing program at the beginning and the end of the program of study and to compare the student's perception of their competency at the end of the program of study with the unit-based nurses expert's perception of the students nursing practice competency. A quantitative pre-post intervention design was used to measure the perception of students at the beginning (T-1) and the end (T-2) of their program of study in nursing. Using Benner's domains of nursing practice, there was a significant difference in self-perception at the beginning and the end of the program. At the end of the program, the unit-based nurse expert rated the student's nursing practice higher on all domains, as compared to the student self-rating. The nursing practice competency of these students was quantified. It is interesting to note that self-rating at the end of the program of study were just below the midpoint of the scale. However, the scoring on a global item of how competent are you to begin practicing as a professional nurse was scored higher than any of the individual domains of practice. © 2010 Elsevier Inc. All rights reserved.